THE EFFECT OF SERVICE QUALITY, FINANCIAL SELF-EFFICACY AND FINANCIAL INCLUSION ON CUSTOMER SATISFACTION AT BANK BRI MATARAM BRANCH - Oktarianti, Ni Putu; Lestari, Baiq Anggun Hilendri; Noviawan, Lalu Andika (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
The purpose of this study is to see the influence of service quality, financial self-efficacy, and financial inclusion on customer satisfaction of Bank BRI Mataram branch. The population in this study is Bank BRI Mataram branch customers and the number of samples is 100 respondents using the Non Probability Sampling method and the technique used is Accidental Sampling. Data collection was carried out by distributing questionnaires online. The data analysis technique used was multiple regression analysis and based on the analysis, it was found that the quality of service and financial inclusion had a positive and significant effect on customer satisfaction while financial self-efficacy did not have a significant effect on customer satisfaction at Bank BRI Mataram branch.